2003
DOI: 10.1021/jp0225626
|View full text |Cite
|
Sign up to set email alerts
|

Long Range Collisional Energy Transfer from Highly Vibrationally Excited Pyrazine to CO Bath Molecules:  Excitation of the v = 1 CO Vibrational Level

Abstract: Collisional energy transfer from highly vibrationally excited pyrazine to CO bath molecules has been studied by use of an infrared diode laser to probe the vibrational, rotational, and translation degrees of freedom of scattered CO molecules. Here the excitation of the CO (V ) 1) bath molecule vibrational state is investigated after a collision with highly excited, vibrationally "hot" pyrazine. Only a small amount of rotational and translational excitation accompanies the production of CO (V ) 1), implicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Chapman et al 41,42 investigated the collisional energy transfer between highly excited pyrazine (E vib ) 40 332 cm -1 ) molecules and CO bath molecules. Their calculation results showed qualitative agreement with the diode laser experiments of Flynn and co-workers 44 and indicated that energy-transfer properties depend on the initial rotational state of the CO. Luther et al 38,39 conducted trajectory calculations for the collisional quenching of hot pyrazine with various polyatomic colliders and investigated the temperature dependence of collisional energy transfer. Luther's studies highlight the importance of pyrazine rotational energy gain as part of the supercollision relaxation process.…”
Section: Introductionsupporting
confidence: 75%
“…Chapman et al 41,42 investigated the collisional energy transfer between highly excited pyrazine (E vib ) 40 332 cm -1 ) molecules and CO bath molecules. Their calculation results showed qualitative agreement with the diode laser experiments of Flynn and co-workers 44 and indicated that energy-transfer properties depend on the initial rotational state of the CO. Luther et al 38,39 conducted trajectory calculations for the collisional quenching of hot pyrazine with various polyatomic colliders and investigated the temperature dependence of collisional energy transfer. Luther's studies highlight the importance of pyrazine rotational energy gain as part of the supercollision relaxation process.…”
Section: Introductionsupporting
confidence: 75%
“…The model systems chosen for study are pyrazine + Ar and ethane + Ar. In its ground electronic state, pyrazine is approximately an oblate symmetric top and has been the subject of numerous energy transfer experiments , and several previous QCT studies. , Ethane, a prolate symmetric top, has been a benchmark for experimental and theoretical studies of unimolecular and recombination reactions. ,, It has also been used for QCT studies of energy transfer. ,, …”
Section: Introductionmentioning
confidence: 99%
“…With some modeling, the P ( E , E ‘) function (or at least its higher energy tail) can be extracted from the experiments , more recent studies have investigated cold collision partners CO, , H 2 O, , and DCl …”
Section: Introductionmentioning
confidence: 99%
“…With some modeling, the P(E,E′) function (or at least its higher energy tail) can be extracted from the experiments. 41 Extensive work has been carried out studying relaxation of hot pyrazine by collision with CO 2 ; [34][35][36][37][38][39][42][43][44][45][46] more recent studies have investigated cold collision partners CO, 40,47 H 2 O, 48, 49 and DCl. 50 There is a long history of using classical trajectory methods to explore these systems: major contributions have been made by Gilbert, Lim and co-workers, [51][52][53][54][55][56] Lenzer, Luther, and coworkers, [57][58][59][60] and Bershtein, Oref and co-workers, [61][62][63][64][65][66][67] and others.…”
Section: Introductionmentioning
confidence: 99%